2002
DOI: 10.1002/path.1056
|View full text |Cite
|
Sign up to set email alerts
|

Authors' reply

Abstract: α,α′‐Diactivated cyclic‐ or acyclic ketones undergo a chemoselective base promoted (K2CO3, DBU) one‐pot C−C cycloalkylation, with 1,3‐ and 1,4‐dihalides having a cis‐like fixed configuration. This reaction gives highly functionalized bicyclo[3.2.1]octan‐9‐one and bicyclo[4.2.1]nonan‐9‐one derivatives, which are easily transformed to seven‐ and eight‐membered rings through a high yield retro‐Dieckmann cleavage. Starting from trans‐1,4‐dibromo‐2‐butenes, the transformation is governed by stereoelectronic factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 50 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…The reported age of incidence is from 40 to 70 years, with a higher incidence over 60 years of age. All the tumors described showed morphological and immunohistochemical similarities to the breast metastases of pulmonary small cell carcinoma, the most distinguishing feature are the absence of primary small cell cancer elsewhere (4,6). The histogenesis is not clear, because the neuroendocrine cells in normal breast have not been proven conclusively (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The reported age of incidence is from 40 to 70 years, with a higher incidence over 60 years of age. All the tumors described showed morphological and immunohistochemical similarities to the breast metastases of pulmonary small cell carcinoma, the most distinguishing feature are the absence of primary small cell cancer elsewhere (4,6). The histogenesis is not clear, because the neuroendocrine cells in normal breast have not been proven conclusively (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that SCNC of breast is a variant of metaplastic carcinoma arising from usual lobular or ductal carcinoma because of its dimorphic picture (4). However other authors believe that SCNC is a distinct type of breast carcinoma different from the usual types of carcinoma, with variable degrees of neuroendocrine differentiation which carries worse prognosis (2,6). Some authors claim that the presence of an in situ carcinoma, with areas of ductal, lobular, or papillary differentiation within the breast is highly suggestive of a primary breast rather than a metastatic tumor (6,8,9), however this criterion was not met in most published descriptions of this rare tumor (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations